Overcoming obstacles, we bid farewell to Maturana and present our newest issue. - Farias, Miguel (Árboles y Rizomas, 2021)
The editor describes the social and political context in the edition of this new issue, bids farewell to Humberto Maturana, highlights his contribution to the intelectual debate and presents the contents of Volume III, Issue 1.